Review of the genus Bampura Tschorsnig (Diptera: Tachinidae), with the description of a new species from Iran - Gilasian, Ebrahim; Ziegler, Joachim; Parchami-Araghi, Mehrdad (Zootaxa, 2019)
The new species Bampura breviaristata Gilasian & Ziegler sp. nov. is described from Karkheh National Park, Khuzestan, Iran. A first full description of the male of Bampura angustigena Tschorsnig and an identification key to both known species of Bampura Tschorsnig are provided. The male terminalia of the examined species of the genera Amnonia Kugler, Atylomyia Brauer, Bampura Tschorsnig and Paratryphera Brauer & Bergenstamm are illustrated and compared. A new taxonomic placement for the genus Bampura, as a member of the tribe Ethillini in the subfamily Exoristinae, is proposed and discussed. The tube-like basiphallus is found to be a new synapomorphic character state for the Paratryphera Brauer & Bergenstamm group of genera.